TREATY OF LAUSANNE: THE TOOL OF MINORITY PROTECTION FOR THE CHAM ALBANIANS OF GREECE - Gözübenli, Abdullah Sencer; Çavuşoğlu, Halim (PEOPLE: International Journal of Social Sciences, 2018)
Cham Albanians, a predominantly Muslim sub-group of Albanians who originally reside in the coastal region of Southern Epirus in Greece’s border region with Albania, had been expelled from Greece twice.As the majority of Cham Albanians were Muslim, they were treated with the same contempt as ethnic Turks living in Greece. According to official data, 3.000 of them were transferred to Turkey as part of the Greek-Turkish population exchange according to the Convention Concerning the Exchange of Greek and Turkish Populations signed at Lausanne on 30 January 1923. Articles 37 to 44 of the Lausanne Peace Treaty attribute substantive rights for exempted Muslims in Greece and non-Muslims in Turkey from the Greek-Turkish population exchange and 17,008 of them wereexempted from the exchange. In this paper, legal status of Muslim Cham Albanians of Greece that were exchanged with Orthodox minority that lived in Turkey after World War I and exiled from Greece after World War II, will be analyzed. This paper aims to emphasize thatMuslim Cham Albanians of Greeceare already recipients of special rights as a subject of law, according to the Treaty of Lausanne (1923) that guarantees the rights of the Muslim minority in Greece. We find very important to analyze Cham Question in the context of the Treaty of Lausanne while Greek government insists that the minority is not “Turkish” but “Muslim” to justify banning associations that include the word “Turk”.